Diagnostic yield and clinical impact of exome sequencing in early-onset scoliosis (EOS). - Zhao, Sen; Zhang, Yuanqiang; Chen, Weisheng; Li, Weiyu; Wang, Shengru; Wang, Lianlei; Zhao, Yanxue; Lin, Mao; Ye, Yongyu; Lin, Jiachen; Zheng, Yu; Liu, Jiaqi; et al. (J Med Genet, 2021)
BACKGROUND: Early-onset scoliosis (EOS), defined by an onset age of scoliosis less than 10 years, conveys significant health risk to affected children. Identification of the molecular aetiology underlying patients with EOS could provide valuable information for both clinical management and prenatal screening. METHODS: In this study, we consecutively recruited a cohort of 447 Chinese patients with operative EOS. We performed exome sequencing (ES) screening on these individuals and their available family members (totaling 670 subjects). Another cohort of 13 patients with idiopathic early-onset scoliosis (IEOS) from the USA who underwent ES was also recruited. RESULTS: After ES data processing and variant interpretation, we detected molecular diagnostic variants in 92 out of 447 (20.6%) Chinese patients with EOS, including 8 patients with molecular confirmation of their clinical diagnosis and 84 patients with molecular diagnoses of previously unrecognised diseases underlying scoliosis. One out of 13 patients with IEOS from the US cohort was molecularly diagnosed. The age at presentation, the number of organ systems involved and the Cobb angle were the three top features predictive of a molecular diagnosis. CONCLUSION: ES enabled the molecular diagnosis/classification of patients with EOS. Specific clinical features/feature pairs are able to indicate the likelihood of gaining a molecular diagnosis through ES.

TBX6-associated congenital scoliosis (TACS) as a clinically distinguishable subtype of congenital scoliosis: further evidence supporting the compound inheritance and TBX6 gene dosage model. - Liu, Jiaqi; Wu, Nan; Yang, Nan; Takeda, Kazuki; Chen, Weisheng; Li, Weiyu; Du, Renqian; Liu, Sen; Zhou, Yangzhong; Zhang, Ling; Liu, Zhenlei; Zuo, Yuzhi; et al. (Genet Med, 2019)
PURPOSE: To characterize clinically measurable endophenotypes, implicating the TBX6 compound inheritance model. METHODS: Patients with congenital scoliosis (CS) from China(N = 345, cohort 1), Japan (N = 142, cohort 2), and the United States (N = 10, cohort 3) were studied. Clinically measurable endophenotypes were compared according to the TBX6 genotypes. A mouse model for Tbx6 compound inheritance (N = 52) was investigated by micro computed tomography (micro-CT). A clinical diagnostic algorithm (TACScore) was developed to assist in clinical recognition of TBX6-associated CS (TACS). RESULTS: In cohort 1, TACS patients (N = 33) were significantly younger at onset than the remaining CS patients (P = 0.02), presented with one or more hemivertebrae/butterfly vertebrae (P = 4.9 × 10), and exhibited vertebral malformations involving the lower part of the spine (T8-S5, P = 4.4 × 10); observations were confirmed in two replication cohorts. Simple rib anomalies were prevalent in TACS patients (P = 3.1 × 10), while intraspinal anomalies were uncommon (P = 7.0 × 10). A clinically usable TACScore was developed with an area under the curve (AUC) of 0.9 (P = 1.6 × 10). A Tbx6 mouse model supported that a gene dosage effect underlies the TACS phenotype. CONCLUSION: TACS is a clinically distinguishable entity with consistent clinically measurable endophenotypes. The type and distribution of vertebral column abnormalities in TBX6/Tbx6 compound inheritance implicate subtle perturbations in gene dosage as a cause of spine developmental birth defects responsible for about 10% of CS.